Pluralismo vivo: lived religious pluralism and interfaith dialogue in Rome - Lindsay, Jennifer (2018)
This ethnography of interreligious dialogue in Rome is concerned with how interfaith encounters and social transformation are dialectically constructed and enacted. The network of Roman interfaith organizations is placed in a Durkheimian framework as a moral community with distinct rituals and sacred objects, referred to as the "interfaith society." The interfaith society described here is distinctly shaped by its location in Rome: the neighboring Vatican, engrained cultural Catholicism, and-through global migratory patterns distinct to the late 20th century-the inundation of non-Catholic religions into Italy. This research analyzed the differences that exist between elite institutional events and informal grassroots (di base) gatherings, noting the way third sector nonprofits form a "hinge" between the two. In-depth examination of the publishing cooperative and program office Confronti shows the evolution of Catholic ecumenical efforts into today's interfaith society. It also shows the value of creative dialogue as a form of interfaith engagement. This exploration is based upon interviews with 52 participants across these settings, participant-observation of interfaith practices, and interviews with 17 Romans who do not practice dialogue. Interfaith encounters and interviews with 25 dialoguers in Israel and Palestine illustrate the difference geographical and sociopolitical context can make in the practice of dialogue, and demonstrate that dialogue is framed in both settings as a method to disrupt historical patterns of stereotyping and objectification. This study finds that interfaith dialogue can best be understood by examining its processes and asking what they mean for participants, rather than looking for "metrics." Encounters across religious difference are found to require intention, leadership, and repetition in order to establish a "safe haven." Participants speak of their goals in terms of "humanizing" the other and striving for "mutual recognition." Each of these discursive goals is explored through the narrative data gathered. They are found to be best understood not by measurement of their "success," but as shared sacred values that bind together the interfaith society. The repeated, communal invocation of these sacred values signifies to the members of the community that they belong to the collective, solidifying also awareness of who is not in their group